DETERMINING AND ANALYSIS OF AZIMUTHAL COEFFICIENTS QI FOR THE SEISMICALLY ACTIVE TRANSCARPATHIANS - Kozlovskyy, E.; Malytskyy, D.; Pavlova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of this paper is to clarify the velocity model of the Transcarpathian seismic region. The model will further be implemented in neuralnetwork modelling to calculate and verify the depth and distribution of earthquake foci. There has been carried out an analysis of seismic wave propagation in different directions across the Transcarpathian seismic region. Being an important parameter indicative of the direction of wave propagation in a natural medium, the azimuthal coefficient qі has proved to be efficient in developing a training neural network set. Two methods of selecting sectors have been shown, based either on the location of a seismic station or a seismic event area. We have calculated average values of the azimuthal coefficient qі for sectors with close values of qі for one-, two- and three-layered media according to the depth of earthquake foci in each of the three layers. With three-layered media covering earthquake foci depths of 8,000-9,000 m, the calculations accurately reflect local seismic events in the Carpathians. An average layer thickness h and an average layer velocity v were calculated separately for each E-S pair (epicenter - seismic station). Conventional combining of layers was used as a method of calculating the third layer azimuth coefficient qі. The calculations were made for direct P-waves (similar calculations can be made for S-waves). We have suggested an interpretation of the obtained results and their practical implications. It has been demonstrated how the azimuthal coefficient can be used in analysing the parameters of media.